2021
DOI: 10.2147/pgpm.s309846
|View full text |Cite
|
Sign up to set email alerts
|

Ferroptosis-Related Gene Signature: A New Method for Personalized Risk Assessment in Patients with Diffuse Large B-Cell Lymphoma

Abstract: Diffuse large B-cell lymphoma (DLBCL) is a genetically heterogeneous disease, which makes prognostic prediction challenging. The rapid development of research on ferroptosis provides the possibility of its use in prognosis in cancer patients. The aim of the current investigation was to perform a systematic study of ferroptosis and DLBCL prognosis to identify prognostic biomarkers in DLBCL. Materials and Methods: A total of 884 DLBCL patients from the Gene Expression Omnibus database were included in this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Few preceding studies implied that numerous genes might control provoked ferroptosis and their association with DLBCL patients' OS. 16 For instance, GPX4-positive and 8-hydroxydeoxyguanosine-negative patients had a significantly poor prognosis. And GPX4 overexpression inhibits ROS-induced cell death in DLBCL.…”
Section: Discussionmentioning
confidence: 99%
“…Few preceding studies implied that numerous genes might control provoked ferroptosis and their association with DLBCL patients' OS. 16 For instance, GPX4-positive and 8-hydroxydeoxyguanosine-negative patients had a significantly poor prognosis. And GPX4 overexpression inhibits ROS-induced cell death in DLBCL.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, HIF1A was associated with increased tumor immunity and aggressive phenotypes in human cancers ( Chen et al, 2020 ). Ferroptosis-related genes associated with the overall survival in patients with diffuse large B-cell lymphoma have also been reported ( Chen H. et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The addition of CXCL2 enhances CLL cell survival. Chen reported that CXCL2 is a significant ferroptosis-related gene signature that can effectively classify DLBCL into different risk groups in terms of survival rate ( 14 ). Ferroptosis is a type of autophagy-dependent cell death.…”
Section: Discussionmentioning
confidence: 99%
“…The action of divalent iron and ester oxygenase catalyzes unsaturated fatty acids that are highly expressed on the cell membrane, leading to lipid peroxidation and inducing ferroptosis ( 10 ). Rapidly developing ferroptosis studies suggest the possibility of its prognostic significance in several cancers ( 11 14 ). Tumor cells are iron addicted, which means they are more dependent on iron than normal cells.…”
Section: Introductionmentioning
confidence: 99%